Etude Phytochimique Et De Cytotoxicité De Quelques Plantes Utilisées Dans Le Traitement De La Stérilité Féminine Au Sud-Bénin - Houmènou, Victorin; Adjatin, Arlette; Assogba, Fidèle; Gbénou, Joachim; Akoègninou, Akpovi (European Scientific Journal, ESJ, 2018)
The most cited plant drugs during an ethnobotanical survey conducted for traditional healers and resource persons in southern Benin, used in the treatment of female infertility, were the subject of a phytochemical screening. It aims to determine the chemical substances that are conferred on the plants. These chemical substances are the pharmacological properties that are used for the treat of ailment recognized as being the origin of this disease. As a result, we studied the cytotoxicity of each herbal drug. In total, the organs of 17 plant species involved in this study are Aframomum melegueta, Allium cepa, Anchomanes deformants, Baphia nitida, Carissa spinarum, Elaeis guineensis, Garcinia cola, Kigelia africana, Monodora myristica, Morinda lucida, Musa sapientum, Olax subscorpioidea, Piper guineense, Pterocarpus erinaceus, Pupalia lappacea, Tetrapleura tetraptera, Xylopia aethiopica. The results obtained indicate that the richness in phytochemical element is a function of the species. Thus, Aframomum melegueta, Garcinia kola, Monodora myristica, Tetrapleura tetraptera, Xylopia aethiopica, and Anchomanes difformis are rich in catechin and/or gallic tannins, mucilages, reducing compounds, anthocyanins and/or leucoanthocyanins. On the other hand, no drugs is at same time rich in free anthracenics, steroids and / or terpernoids, alkaloids, saponosides, and quinone derivatives. The calculated CL50 values for each of the plant organs are all greater than 0.1 mg / ml. None of them is toxic. However, the non-toxicity of an herbal drug does not mean the same with the multispecies recipe in which it is used. Pharmacological tests of the various recipes used are also of significant importance.